Selectivity of acephate and propaphos to the wolf spider, Pardosa pseudoannulata (Boes et Strand) and brown planthopper, Nilaparvata lugens (Stal). Part I. Toxicity, anticholinesterase activity, and bioactivation - Thang, M.H (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2000)
The toxicity, anticholinesterase activity, and the rate of bioactivation of acephate and propaphos were examined in the predatory wolf spider, Pardosa pseudoannulata, and its prey, the brown planthopper, Nilaparvata lugens, to determine the mechanisms for selectivity (lower toxicity). Based on LD50 values, acephate and propaphos were markedly less toxic to P. pseudoannulata than N. lugens. Both insecticides were poor inhibitors in vitro of acetylcholinesterase but were effective in vivo due to their bioactivation into more potent acetylcholinesterase inhibitor(s) through the mixed function oxidase system. Acephate and propaphos were activated into methamidophos and propaphos sulfoxide, respectively. The in vitro oxidative bioactivation of these compounds was distinctly higher in N. lugens than in P. pseudoannulata. The higher in vivo acetylcholinesterase inhibition with the corresponding higher toxicity for N. lugens than for P. pseudoannulata was associated with the higher mixed function oxidase activation of acephate and propaphos. The lower sensitivity of P. pseudoannulata AChE to propaphos is also involved in propaphos selectivity. The selectivity of acephate and propaphos to P. pseudoannulata could be partly attributed to the slower conversion to a more potent acetylcholinesterase inhibitor in the spider than in the brown planthopper.